Kitab Hadis Nusantara: Studi Atas Kitab Al-Arba’una Haditsan Karya Muhammad Yasin Al-Fadani, Padang - Ilyas Daud (Al-Ulum, 2016)
This paper discusses about the characteristic of Hadith book written by on of scholars of archipelago named Sheikh Muhammad Yasin Al-Fadani which is the book of Arba'una Haditsan min Arba'ina Kitaban an Arba'ina Syaikhan. This study shows that the motivation of al-Fadani wrote this book iscause follows the predecessor scholars who compiled the book with forty hadith. This book have some characteristics;first, before presenting the honor tradition, its beginning with naming as the main reference book and author. Then the description of the genealogical chain of transmission that is long enough. The length of the description of this sanad is caused the explaining by al-Fadani is not departing from Imam mukharij as pentadwin hadith, but starting from Al-Fadani own. Secondly, when referring to the theory or concept of the preparation hadith method, the preparation book of Al-Arba'una Haditsan is follow Mustakhraj method. In terms of quality of knowledge, al-Fadani widely recognized for both of Arab scholars and the archipelago as scholar who mastered the science of hadith, especially sanad of hadith.